Egy kvalitatív kutatás eredményei a dél-alföldi régió egyes mezőgazdasági vállalkozásainál - Vincze-Lendvai, Edina; Szűcs, Kata (Jelenkori Társadalmi és Gazdasági Folyamatok, 2013)
In 2004 Hungary ha s afiiliated to the European Union. The country has been the part of a big economic integration. The (agri)products ofth e other counlries can flow without bordér. In our work we was wondered the effect of the connection to EU. In our investigation we made seven deep interviews with managers of the Hungárián agricultural, or food enterprises about the changes.